2017
DOI: 10.1007/s00253-017-8552-6
|View full text |Cite
|
Sign up to set email alerts
|

CYP109E1 is a novel versatile statin and terpene oxidase from Bacillus megaterium

Abstract: CYP109E1 is a cytochrome P450 monooxygenase from Bacillus megaterium with a hydroxylation activity for testosterone and vitamin D3. This study reports the screening of a focused library of statins, terpene-derived and steroidal compounds to explore the substrate spectrum of this enzyme. Catalytic activity of CYP109E1 towards the statin drug-precursor compactin and the prodrugs lovastatin and simvastatin as well as biotechnologically relevant terpene compounds including ionones, nootkatone, isolongifolen-9-one,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…CYP108D1 from Novosphingobium aromaticivorans DSM12444 was reported to have the activity in the oxidation of polycyclic aromatic hydrocarbons, such as phenanthrene, biphenyl, and phenylcyclohexane [30]. CYP108A1 can effectively hydroxylate the terpene for α-terpineol oxidation [31]. CYP108N7 from Rhodococcus NBRC 100605 is also able to catalyze the epoxidation, hydroxylation, demethylation, and dehalogenation of low molecular weight PAHs and their products [32].…”
Section: Discussionmentioning
confidence: 99%
“…CYP108D1 from Novosphingobium aromaticivorans DSM12444 was reported to have the activity in the oxidation of polycyclic aromatic hydrocarbons, such as phenanthrene, biphenyl, and phenylcyclohexane [30]. CYP108A1 can effectively hydroxylate the terpene for α-terpineol oxidation [31]. CYP108N7 from Rhodococcus NBRC 100605 is also able to catalyze the epoxidation, hydroxylation, demethylation, and dehalogenation of low molecular weight PAHs and their products [32].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the steroid hydroxylating CYP109E1 from B. megaterium (36% identity to CYP109Q5) showed that this enzyme is more closely related to the steroid hydroxylase CYP106A1 in comparison with the already characterized CYP109 enzymes (J o zwik et al, 2016). Classification into a P450 family thus represents a strong evidence for a particular substrate spectrum; this is reflected by CYP109B1 and CYP109E1 that also functionalize a broad spectrum of substrates including steroids, fatty acids and terpenes (Girhard et al, 2010;Putkaradze et al, 2017). However, the preferences or natural substrates may differ in large and heterogeneous P450 families such as the CYP109 family.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that bacterial cytochrome P450s, among them the hydroxylase CYP109E1 from Bacillus megaterium, can oxidize various apocarotenoids (Khatri et al 2010;Litzenburger and Bernhardt 2016) including ionones (Putkaradze et al 2017). Therefore, B. megaterium expressing CYP109E1…”
Section: Production Of Hydroxylated C 13 -Apocarotenols and Their Conmentioning
confidence: 99%
“…In addition, 3-hydroxy-α-ionol, 4-hydroxy-β-ionol, 3-hydroxy-α-ionone, 4-hydroxy-βionone, 3-hydroxy-α-damascone and 4-hydroxy-β-damascone were tested, which were produced by P450-catalyzed biotransformation using Bacillus megaterium (Putkaradze et al 2017). For the substrate screening, 50 µl crude protein extract, 100…”
Section: Substrate Screening By Lc-msmentioning
confidence: 99%
See 1 more Smart Citation